2008
DOI: 10.1007/s00125-008-1100-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral benfotiamine plus α-lipoic acid normalises complication-causing pathways in type 1 diabetes

Abstract: Aims/hypothesis We determined whether fixed doses of benfotiamine in combination with slow-release α-lipoic acid normalise markers of reactive oxygen species-induced pathways of complications in humans. Methods Male participants with and without type 1 diabetes were studied in the General Clinical Research Centre of the Albert Einstein College of Medicine. Glycaemic status was assessed by measuring baseline values of three different indicators of hyperglycaemia. Intracellular AGE formation, hexosamine pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 11 publications
(13 reference statements)
3
66
0
2
Order By: Relevance
“…Arora et al [56] Thiamine Improved endothelial-dependent vasodilation in subjects with impaired glucose tolerance and in T2DM patients Du et al [57] Benfotiamine + α-lipoic acid Normalization of AGEs production and prostacyclin synthase activity and decreases hexosamine-modified protein in monocytes without changing glycaemic control in T1DM González-Ortiz et al [58] Thiamine…”
Section: Treatment Resultsmentioning
confidence: 99%
“…Arora et al [56] Thiamine Improved endothelial-dependent vasodilation in subjects with impaired glucose tolerance and in T2DM patients Du et al [57] Benfotiamine + α-lipoic acid Normalization of AGEs production and prostacyclin synthase activity and decreases hexosamine-modified protein in monocytes without changing glycaemic control in T1DM González-Ortiz et al [58] Thiamine…”
Section: Treatment Resultsmentioning
confidence: 99%
“…According to these studies antioxidant supplementation such as vitamin use, may not be the ideal antioxidant strategy in human diabetic nephropathy. However, some studies that used combined antioxidants therapy or antioxidant with anti-inflammatory agent showed that improvement of albuminuria, HbA1C and MDA in diabetic patients (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Pyridoxine is also involved in the protein metabolism and partly in the fat metabolism. Both vitamins potentiate the action of each other [1, 8,9,10,12,13].…”
Section: The Studies In Selecting the Optimal Technology For Obtaininmentioning
confidence: 99%